Interferensi Bahasa Daerah dalam Pembelajaran Bahasa Arab: Analisis Dampak pada Struktur Sintaksis dan Pemahaman Semantik - Hindun, Hindun; Humaidi, Humaidi (Qismul Arab: Journal of Arabic Education, 2024)
In learning Arabic, students will encounter and experience difficulties using language elements because they use local language patterns in the language being learned. This is called language interference. It leads to the deterioration of the language. The researcher intends to identify the types of interference, the factors affecting interference, and the solutions to avoid it. The method used is a descriptive analysis approach (qualitative). This research used the following tools: interview, observation, and documentation. The most important thing from the study results is that the types of language interference that often occur are phonetic, grammatical, semantic and word repetition. Factors that influence this interference are the environment, inherited habits in language interference and lack of correct vocabulary application. Some solutions to this problem are to increase listening and watching Arabic videos, films and songs, and increase applying and practising correct Arabic speech and according to Arabic grammar rules, and increase memorizing and understanding Arabic vocabulary